Certyfikaty inwestycyjne w portfelach otwartych funduszy emerytalnych - Miziołek, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
According to "Law of 28 August 1997 on organization and operation of pension funds" open pension funds (OPFs) may invest in investment certificates issued by closed-end investment funds maximum 10 percent of their assets. At the end of 2006 only 9 OPFs (from 15 operating in Poland) invested in certificates issued by 3 real-estate funds (Arka, Skarbiec and BPH) together hardly 345 millions PLN (about 0,3% of aggregate investment portfolio of OPFs). The main barriers which impede engagement of OPFs in investment certificates are: relatively small value of closed-funds assets, insignificant turnover of certificates on the Warsaw Stock Exchange and legislation (minimum required return). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 270-278